1999
DOI: 10.1016/s1097-2765(01)80007-1
|View full text |Cite
|
Sign up to set email alerts
|

Synip

Abstract: Insulin-stimulated glucose transport and GLUT4 translocation require regulated interactions between the v-SNARE, VAMP2, and the t-SNARE, syntaxin 4. We have isolated a novel syntaxin 4-binding protein, Synip, which specifically interacts with syntaxin 4. Insulin induces a dissociation of the Synip:syntaxin 4 complex due to an apparent decrease in the binding affinity of Synip for syntaxin 4. In contrast, the carboxyterminal domain of Synip does not dissociate from syntaxin 4 in response to insulin stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(65 citation statements)
references
References 52 publications
2
63
0
Order By: Relevance
“…Previously, we reported that Synip binding to syntaxin 4 competes for VAMP2 binding and is therefore mutually exclusive (18). As expected, overexpression of Synip completely prevented the association of VAMP2 with syntaxin 4 before and after glucose stimulation and inhibited glucose-stimulated insulin secretion.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Previously, we reported that Synip binding to syntaxin 4 competes for VAMP2 binding and is therefore mutually exclusive (18). As expected, overexpression of Synip completely prevented the association of VAMP2 with syntaxin 4 before and after glucose stimulation and inhibited glucose-stimulated insulin secretion.…”
Section: Discussionsupporting
confidence: 83%
“…As a control for syntaxin 4 and Synip specificity, we also expressed Synip/WT and examined its binding to syntaxin 1. As reported previously (18), the immunoprecipitation of Synip/WT resulted in the co-precipitation of syntaxin 4 but not syntaxin 1 (data not shown). Together, these data suggest that syntaxin 4 and Synip may both play functional roles in glucosestimulated insulin secretion.…”
Section: Synip Expression In ␤Hc-9supporting
confidence: 86%
See 3 more Smart Citations